Production of the matrix protein of nipah virus in escherichia coli: virus-like particles and possible application in diagnosis. - Senthil, Kumar Subramanian; Tey, Beng Ti; Hamid, Muhajir; Tan, Wen Siang (Elsevier Ltd., 2009)
The broad species tropism of Nipah virus (NiV) coupled with its high pathogenicity demand a rapid search for a new biomarker candidate for diagnosis. The matrix (M) protein was expressed in Escherichia coli and purified using a Ni-NTA affinity column chromatography and sucrose density gradient centrifugation. The recombinant M protein with the molecular mass (Mr) of about 43 kDa was detected by anti-NiV serum and anti-myc antibody. About 50% of the M protein was found to be soluble and localized in cytoplasm when the cells were grown at 30 degrees C. Electron microscopic analysis showed that the purified M protein assembled into spherical particles of different sizes with diameters ranging from 20 to 50 nm. The purified M protein showed significant reactivity with the swine sera collected during the NiV outbreak, demonstrating its potential as a diagnostic reagent.